Forgiveness and atonement: Christ's restorative sacrifice - Rutledge, Jonathan (Routledge studies in analytic and systematic theology, 2022)
"This book analyzes the relationship between forgiveness, atonement, and reconciliation from a Christian theological perspective. Drawing on both theological and philosophical literature, it addresses the problem of whether atonement is required for forgiveness and considers important related concepts such as sin and justice. The author develops a sacrificial model of atonement that connects an understanding of Christian forgiveness with the biblical narrative of Christ's sacrifice and makes reconciliation between God and humanity possible. Offering a fresh and coherent argument, the book will be relevant to scholars of Christian theology, biblical studies, and the philosophy of religion"--